2003
DOI: 10.1183/09031936.03.00057302
|View full text |Cite
|
Sign up to set email alerts
|

A prediction rule to identify allocation of inpatient care in community-acquired pneumonia

Abstract: The current authors developed a new prediction rule based on the five risk classes defined by the Pneumonia Severity Index to identify allocation of inpatient care in community-acquired pneumonia.The decision to hospitalise in low-risk classes (I-III) was unquestionable, if the presence of one or more of the following were evident: arterial oxygen tensionv8.0 kPa (60 mmHg), shock, decompensated coexisting illnesses, pleural effusion, inability to maintain oral intake, social problem, and lack of response to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 33 publications
0
38
0
5
Order By: Relevance
“…The ED staff is composed of full-time physicians of diverse specialities, including ED specialists and primary care physicians. During the study, a guideline for the management of patients with CAP (described in more detail elsewhere [7]) was implemented. Explicit admission-decision criteria were established based on risk classes defined according to the PSI [6] with a series of additional criteria [7].…”
Section: Setting Of Study and Designmentioning
confidence: 99%
“…The ED staff is composed of full-time physicians of diverse specialities, including ED specialists and primary care physicians. During the study, a guideline for the management of patients with CAP (described in more detail elsewhere [7]) was implemented. Explicit admission-decision criteria were established based on risk classes defined according to the PSI [6] with a series of additional criteria [7].…”
Section: Setting Of Study and Designmentioning
confidence: 99%
“…En los pacientes con neumonía la distribución por clase de Fine es muy similar a otros trabajos, quizá con un porcentaje más bajo de pacientes en el grupo V, los más graves (1,3,6,7,22) lo que nos permite hasta cierto punto comparar datos (Tabla I). TABLA V Del total de pacientes que acude a urgencias, un 47% es tratado de forma ambulatoria, de ellos reingresan 17, un 6%.…”
Section: Discussionunclassified
“…Respecto a los pacientes ingresados la tasa de mortalidad global es similar a la descrita en la literatura, entre el 5 y 13% (1,(5)(6)(7)(8)13,24). El porcentaje de fracasos de tratamiento es también comparable a la de otros trabajos realizados en nuestro medio, 15% en el trabajo de Menéndez (20).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In CURB-65 system, the presence of confusion, serum urea value, respiratory rate, blood pressure, and the age of patient are evaluated. It is recommended to hospitalize patients with CURB-65 score of ≥2 or PSI score of 4 and 5; however, the decision of hospitalization is made by the physician considering social indication and clinical picture of the patient [1,[7][8][9]. Indeed, some studies have revealed that these indices vary in clinical practice.…”
Section: Discussionmentioning
confidence: 99%